National Laboratory Biosecurity Assessment and Monitoring Checklist (in the framework of the Biological Weapons Convention) - Yunus, Zalini (Science and Technology Research Institute for Defense (STRIDE), 2018)
Article IV of the Biological Weapons Convention (BWC) mandates that every state party shall “take any necessary measures to prohibit and prevent the development, production, stockpiling, acquisition or retention of biological agents or equipment for the purpose of employing them as a biological weapon”. Malaysia as a state party to the BWC has taken many initiatives to strengthen national measures to fulfil our obligations towards the BWC. The Science and Technology Research Institute for Defence (STRIDE), Ministry of Defence, as the lead technical agency in Malaysia for the BWC, has been actively promoting and implementing national measures focusing on biosecurity, biorisk management and biothreats reduction. STRIDE has identified the need to address the concern of ensuring laboratory safety and security and establishing stronger systems to detect and prevent deliberate release of biological agents. As laboratory capacity and capabilities grow, additional attention should be paid to the potential for accidental and deliberate releases of valuable biological materials and on the broad needs around laboratory operational, regulatory, and physical security as well as personnel monitoring programmes. It is crucial for laboratories in the country that are handling valuable biological materials to develop a comprehensive biorisk management programme and be given the necessary support and tools to assess and monitor their laboratory biosecurity implementation. With this in mind, the development of a National Laboratory Biosecurity Assessment and Monitoring Checklist was proposed by STRIDE. Expert guidance and assistance was granted to Malaysia through the European Union Extended Assistance Programmes offered as part of the European Union Council Decision 2016/51 in support of the Biological Weapons Convention (BWC). The main objective of this checklist is to enhance Malaysia’s capacity in the area of biosecurity by developing a comprehensive biosecurity checklist for laboratory assessments and monitoring. The checklist covers the eight pillars of biosecurity; management, biosecurity awareness, physical security, accountability for materials, information security, transport security, personnel reliability, and emergency response. The checklist will assist laboratories, especially high containment laboratories that are handling valuable biological materials, to assess the current level of biosecurity and identify gaps in the existing biosecurity programme; monitor the biosecurity programme efficiency and effectiveness as well as ensure compliance with national and international standards. Through this practical approach, institutions will be able to conduct assessments and monitor their biosecurity programme to ensure they have the necessary biosecurity measure implemented to prevent potentials for accidental and deliberate releases of valuable biological materials. This checklist is also intended for assessors who are performing laboratory biosecurity assessments. This initiative will ensure a sustainable culture of scientific responsibility and most importantly show Malaysia’s commitment to fulfil national obligations and enhance Malaysia’s national capacity to implement the BWC.